From Boardroom to Stadium: How International Sports Organizations Recruit Talent (International Journal of Scientific Research and Management (IJSRM), 2025)
Recruitment forms the basis of achievement for international sports organizations and both board members and athletes in the playing area. In this research, the approaches, issues and trends that influence the identification, sourcing and management of human capital in these organizations in the chasm of a competitive and fast growing environment are examined. It explores the provision of boardroom executives and actual players; emphasizes the place of technology, cultural diversity, and ethical issues in the present day recruitment. By analysing strategic, IT and SAP recruitment successes and failures the research provides understanding on sustainable talent sourcing and changes happening in the industry. The results support the need for the use of analytics, diversity, and creativity to achieve strategic human resource management in recruitment. The purpose of this research is to develop a broad understanding of the diverse nature of the recruitment challenges within sports whilst focusing on it being a strategic factor for improved operational output and organisational competitive advantage.